PEMULIAAN TANAMAN MURBEI UNTUK ULAT SUTERA (Mulberry Improvement for Silk Worm Feed) - , Budi Santoso ([Yogyakarta] : Fak. Kehutanan UGM, 2000)
To improve mulberry leave production and quality, the role of genetic improvement is very important mainly for producing new mulberry varieties suitable for siik worm fodder. Genetic improvement can be carried out by controlled hibridization which is simpler and less expensive compared with invitro improvement. The South Sulawesi Forest Research Institute has been carried out mulberry improvement program since 1990 and produced a number of new mulberry varieties